2019
DOI: 10.1109/jlt.2018.2870038
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity Transmission With Few-Mode Fibers

Abstract: We experimentally investigate high-capacity fewmode fiber transmission for short and medium-haul optical links. In separate experiments, we demonstrate C + L band transmission of 283 Tbit/s over a single 30 km span and 159 Tbit/s over 1045 km looped transmission in a graded-index three mode fiber. The first experiment reached a data-rate per fiber mode within 90% of the record data-rates reported in the same transmission bands for single-mode fiber. The second experiment demonstrated the feasibility of reachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 24 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…This combination of WDM and FMF supports high speed transmission that can reach up to hundreds of Tera bit/s [40], [41]. For instance, three modes graded-index FMF transmission over C and L bands have been demonstrated to achieve data rates of 159 Tbit/s [40] and 280 Tbit/s [41]. Furthermore, SDM networks based on multi-core fibers and FMF increase the transmission capacity dramatically using a single optical fiber cable [42], [43].…”
Section: Opm In Fmf-based Networkmentioning
confidence: 97%
See 1 more Smart Citation
“…This combination of WDM and FMF supports high speed transmission that can reach up to hundreds of Tera bit/s [40], [41]. For instance, three modes graded-index FMF transmission over C and L bands have been demonstrated to achieve data rates of 159 Tbit/s [40] and 280 Tbit/s [41]. Furthermore, SDM networks based on multi-core fibers and FMF increase the transmission capacity dramatically using a single optical fiber cable [42], [43].…”
Section: Opm In Fmf-based Networkmentioning
confidence: 97%
“…2, where different WDM signals can be transmitted at the same band using different modes [39]. This combination of WDM and FMF supports high speed transmission that can reach up to hundreds of Tera bit/s [40], [41]. For instance, three modes graded-index FMF transmission over C and L bands have been demonstrated to achieve data rates of 159 Tbit/s [40] and 280 Tbit/s [41].…”
Section: Opm In Fmf-based Networkmentioning
confidence: 98%
“…In [9], an adaptive MIMO filtering techniques are proposed to de-multiplex the signals upon different modes or cores, and to dynamically compensate for the DMGD plus mode-MDLvia DSP. In [10], it is shown that the MDM system together with MIMO DSP has the potential capability of enhancing capacity, or reducing the transmission energy by one to two orders of magnitude. In addition, advanced digital signal processing (DSP) technology has also demonstrated its potential to mitigate the MDL in the MDM system [11]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more convenient communication and connectivity are expected in the next generation communication services such as beyond 5G mobiles. In order to realize such a large capacity data center and access network, novel photonic integrated circuits (PICs), which enable ultra‐fast and large capacity communication, are indispensable, besides improving communication capacity owing to newly developed modulation and system technologies . In addition, characteristics such as low cost and energy consumption, and thermal stability at high temperatures are essential if the PICs are to be integrated with other electronic devices such as large‐scale integrated circuits (LSIs).…”
Section: Introductionmentioning
confidence: 99%